Dietary interventions with dietitian involvement in adults with chronic kidney disease: A systematic review. Issue 4 (8th March 2021) - Brown, Tamara J.; Williams, Harriet; Mafrici, Bruno; Jackson, Helena S.; Johansson, Lina; Willingham, Fiona; McIntosh, Ashleigh; MacLaughlin, Helen L.
Abstract: Background: A comprehensive evidence base is needed to support recommendations for the dietetic management of adults with chronic kidney disease (CKD). The present study aimed to determine the effect of dietary interventions with dietitian involvement on nutritional status, well‐being, kidney risk factors and clinical outcomes in adults with CKD. Methods: Cochrane Central Register of Controlled Trials, CINAHL, MEDLINE, PsycINFO and EMBASE.com were searched from January 2000 to November 2019. Intentional weight loss and single nutrient studies were excluded. Risk of bias was assessed using the Cochrane risk‐of‐bias tool. Effectiveness was summarised using the mean difference between groups for each outcome per study. Results: Twelve controlled trials (1906 participants) were included. High fruit and vegetable intake, as well as a multidisciplinary hospital and community care programme, slowed the decline in glomerular filtration rate in adults with stage 3–4 CKD. Interventions addressing nutrition‐related barriers increased protein and energy intake in haemodialysis patients. A Mediterranean diet and a diet with high n ‐3 polyunsaturated fatty acids improved the lipid profile in kidney transplant recipients. Conclusions: A limited number of studies suggest benefits as a result of dietary interventions that are delivered by dietitians and focus on diet quality. We did not identify any studies that focussed on our primary outcome of nutritional status or studies that examined the timing or frequency of the nutritional assessment. This review emphasises the need for a wider body of high‐quality evidence to support recommendations on what and how dietetic interventions are delivered by dietitians for adults with CKD. Abstract : Our systematic review of dietetic interventions for adults with chronic kidney disease highlights the lack of a comprehensive evidence base to support recommendations for the dietetic management of adults with chronic kidney disease.